Expression of long noncoding RNA MALAT1 correlates with increased levels of Nischarin and inhibits oncogenic cell functions in breast cancer - Eastlack, Steven C.; Dong, Shengli; Mo, Yin Y.; Alahari, Suresh K. (PloS one, 2018)
Malat1 is a long noncoding RNA with a wide array of functions, including roles in regulating cancer cell migration and metastasis. However, the nature of its involvement in control of these oncogenic processes is incompletely understood. In the present study, we investigate the role of Malat1 and the effects of Malat1 KO in a breast cancer cell model. Our selection of Malat1 as the subject of inquiry followed initial screening experiments seeking to identify lncRNAs which are altered in the presence or absence of Nischarin, a gene of interest previously discovered by our lab. Nischarin is a well characterized tumor suppressor protein and actively represses cell proliferation, migration, and invasion in breast cancer. Our microarray screen for lncRNAs revealed multiple lncRNAs to be significantly elevated in cells ectopically expressing Nischarin compared to control cancer cells, which have only marginal Nisch expression. Using these cells, we assess how the link between Nischarin and Malat1 affects cancer cell function, finding that Malat1 confers an inhibitory effect on cell growth and migration which is lost following Malat1 KO, but in a Nisch-dependent context. Specifically, Malat1 KO in the background of low Nischarin expression had a limited effect on cell functions, while Malat1 KO in cells with high levels of Nischarin led to significant increases in cell proliferation and migration. In summary, this project provides further clarity concerning the function of Malat1, specifically in breast cancer, while also indicating that the Nischarin expression context is an important factor in the determining how Malat1 activity is governed in breast cancer.